Monitoring system using handwritten sample pressure point - Abdul Hamid, Syamsul Bahrin; Shaharom, Rabiatul Adawiyah (Institute of Research and Journals, 2017)
This paper explores the possibility of using handwritten sample pressure points for robust attendance monitoring. Utilizing robust FSR as the sensing mechanism, this paper investigates the calibration process that has been conducted for using the FSR as an attendance monitoring system. From the investigation, it could be concluded that there is a possibility of using FSR as a sensing mechanism for simple geometric and block alphabet, but further research is still needed for the system cater for cursive handwritten signature.